Track of GPS-Drifter PIRATA-FR35_396 - Ruben Carrasco; Jochen Horstmann; Florent Gasparin; Jerome Llido; Pierre Rousselot; Ildut Pondaven; Sophie Cravatte (PANGAEA, 2026)
As part of its support for the preparation of future surface–current observation missions, CNES is funding the PIRATA–ODYSEA experiment, dedicated to studying ocean surface circulation in the equatorial Atlantic. Launched in March 2025 for several months, the campaign aims to bridge the gap between satellite observations—which target currents within the uppermost meter of the ocean—and the in-situ instruments typically used for calibration/validation (CAL/VAL), which operate at depths of several meters. The campaign also seeks to better characterize the diurnal variability of currents, a key source of aliasing for satellite measurements. The dataset comprises 40 Hereon Lagrangian surface drifters deployed along the equatorial line of the Atlantic Ocean.
In: Carrasco, R et al. (2026): Surface Drifter Data in the Equatorial Atlantic: Positions of Hereon Drifters deployed during PIRATA–ODYSEA experiment [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.990169